The Analysis of Curriculum Ideologies in LGCSE Sesotho Syllabus - Makoa, Malisema Francina (Innovare Journal of Education, 2023)
A curriculum is a prearranged design for teaching negotiated by ability in the light of their skilled knowledge and the context of societal prospects and students’ needs. This paper aims to analyze the curriculum ideologies available in the Sesotho, Lesotho General Certificate of Secondary Education (LGCSE) syllabus and whether Sesotho literature develops the students holistically to fit in society. The paper use document analysis where the LGCSE syllabus aims will be analyzed. The paper has found that the dominating ideology is learner-centered, and social reconstruction does not appear in all aims. Social efficiency and scholarly academic appear in three and two aims, respectively. The aim and the purpose of education are to help learners to change society not only to be academicians, but it seems like this curriculum helps students to develop as individuals instead of developing society as a whole.